DISJUNCTIVE DISTRIBUTION OF ODOCNEMIS PROTINUS (REITTER, 1900), THE FIRST REPRESENTATIVE OF THE GENUS (COLEOPTERA: TENEBRIONIDAE: HELOPINI) IN IRAN - M. V. Nabozhenko; B. Keskin (Юг России: экология, развитие)
Abstract. The first representative of the genus Odocnemis Allard, 1876 – O. protinus (Reitter, 1900) is found in Northern Iran (Gilan Province). To present time the species was known from North Western Anatolia. Close species Odocnemis opertus (Reitter, 1922) is also known from north west of Anatolia. Both species relate with relic oak species Quercus cerris. Iranian population of O. protinus inhabits altitude (1400–1800 m) with relic Qeurcus castaneiformis (species from section cerris). Disjunction in range of O. protinus probably connects with fragmentation of Turgayan flora in Late Miocene (6 Ma). Solid paleodistribution of this species (Southern land of Paratethys) probably was formed in Middle Miocene (12–11 Ma), when was completed connection between Western Asia and Iranian Land. Morphological description with key to opertus species group of the genus Odocnemis and differences for Iranian and Turkish populations of O. protinus are given in the paper.